Le regard féminin : une révolution à l'écran - Brey, Iris (Les Feux, 2609-8113, 2020)
Iris Brey théorise le regard féminin, ou female gaze, une façon de filmer les femmes sans en faire des objets, de partager la singularité des expériences féminines avec tous les spectateurices, quel que soit leur genre, et de renouveler notre manière de désirer en regardant sans voyeurisme. Des joyaux du cinéma à certaines oeuvres plus confidentielles, en passant par quelques séries et films très contemporains, Iris Brey nous invite à nous interroger sur le sens caché des images.
Keywords: approches et analyses; cinéma; com5170; communication; corps; cours; discipline; discours dominant; fem1300; fem3200; premier cycle; regard féminin; sexisme; systèmes d'oppressions; thématiques; violences

Daughters of the dust - Dash, Julie (Cohen Film Collection, 1991)
At the dawn of the 20th century, a multi-generational family in the Gullah community on the Sea Islands off of South Carolina – former West African slaves who adopted many of their ancestors’ Yoruba traditions – struggle to maintain their cultural heritage and folklore while contemplating a migration to the mainland, even further from their roots. The first wide release by a black female filmmaker, DAUGHTERS OF THE DUST was met with wild critical acclaim and rapturous audience response when it initially opened in 1991. Casting a long legacy, DAUGHTERS OF THE DUST still resonates today, most recently as a major in influence on Beyonce’s video album Lemonade. Winner of the Cinematography Award and nominated for the Grand Jury Prize in the Dramatic competition at the Sundance Film Festival. Chosen for preservation by the National Film Preservation Board, USA
Keywords: 1900-1999; amériques; antiracisme; approches et analyses; cinéma; communication; cours; discipline; discours dominant; esclavagisme; fem3200; histoire et politique; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences; états-unis